(untitled) (Research, Society and Development, 2024)
This study sought to analyze the impact of glass fiber angle orientation and glass transition temperature on tear strength in laminates produced by vacuum infusion and manual lamination. The resin was impregnated into the fiberglass fabrics, and the curing temperature was ambient, determined by the characteristic of the resin during the exothermic peak. The laminates were manufactured with a 0º orientation, both by vacuum infusion and manual lamination. Tensile tests, in accordance with ISO 527-5, were carried out to evaluate the longitudinal strength of the laminates. The results showed that the unidirectional (UD) laminate produced by manual lamination outperformed the laminate of the same fabric, but with a vacuum infusion manufacturing process. In particular, the UD - Manual laminate presented a resistance 57.77% higher than the equivalent made by vacuum infusion. The study concluded that, despite theoretical expectations based on calcination and hardness tests, the glass transition temperature was the dominant parameter in laminate strength. Practical results indicated that laminates produced by manual rolling, especially with unidirectional orientation at 0º, demonstrated greater resistance to rupture compared to equivalent laminates produced by vacuum infusion.